Senam Terapeutik Tingkatkan Kesehatan Pasien Penyakit Degeneratif di Kabupaten Bungo - Jhony Hendra; Deka Ismi Mori Saputra; Yessy Fitriani; Diza Sartika; Shilvia Arienda; Iren Arsima Natasya; Karin Okta Aditia (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Degenerative diseases are a major public health problem in Indonesia, especially in Bungo Regency. Various efforts have been made to prevent them, one of which is through gymnastics. Gymnastics is an activity carried out to maximize body function through movement. Gymnastics is the right medium to restore body function and improve the quality of life of degenerative patients through therapeutic gymnastics, including; heart gymnastics, brain gymnastics, rheumatic gymnastics, and diabetes mellitus gymnastics. Gymnastics is very popular among various groups, including the elderly, because it creates a pleasant and joyful atmosphere. The results of interviews with the community service team and partners of the Muara Bungo I Community Health Center UPT revealed that there are still many patients with degenerative diseases. Therefore, the implementation of therapeutic gymnastics is a highly desired need by partners. Solutions to these partner problems include providing assistance on the importance of therapeutic gymnastics for degenerative patients and health checks. The purpose of this community service activity is to improve body function and the quality of life of patients with degenerative diseases. The method used is the interview method. The results of this community service included outreach activities, increased knowledge, and the implementation of therapeutic exercises to improve body function and the quality of life for patients with degenerative diseases. Patients were able to perform therapeutic exercises to maximize their function.